IBN SĪNĀ AND IBN RUSHD’S CONCEPTIONS OF THE SOUL IN LIGHT OF ARISTOTLE’S THEORY OF FOUR CAUSES - Saruhan, Müfit Selim (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
This article undertakes a comparative study of Ibn Sīnā and Ibn Rushd’s conceptions of the soul through the framework of Aristotle’s four causes: material, formal, efficient, and final. Both thinkers draw deeply from Aristotelian psychology, yet their approaches diverge due to different metaphysical and theological commitments. Ibn Sīnā, shaped by Neoplatonic currents, presents the soul as an immaterial, self-subsistent substance that transcends the body and seeks perfection in union with the Active Intellect. This union is achieved through rational contemplation, ethical purification, and intellectual ascent, granting the soul an independent and eternal telos. By contrast, Ibn Rushd interprets the soul in strict continuity with Aristotle’s naturalism, emphasizing its inseparability from the body as its form and actuality. For him, human perfection is realized not in metaphysical transcendence but in civic virtue, rational engagement, and intellectual cultivation within empirical life. The article applies Aristotle’s four causes to their respective models, exploring the ontological, epistemological, and ethical implications of each framework. It further situates their perspectives within broader debates on consciousness, personhood, and moral responsibility, highlighting the enduring relevance of their insights. The study argues that re-examining these classical Islamic philosophies provides valuable resources for contemporary discussions in the philosophy of mind, ethics, and metaphysics.